Construct Validity of the Questionnaire Quality From the Patients Perspective Adapted for Surgical Prostate Cancer Patients. (3rd March 2021) - Christiansen, Ola; Benth, Jūratė Šaltytė; Kirkevold, Øyvind; Bratt, Ola; Slaaen, Marit
Patient-reported experience measures (PREMs) are important to capture the patients' voice. No such measure is routinely used for evaluation after robotic-assisted radical prostatectomy for prostate cancer. The aim of this study was to adapt the short version of the PREM questionnaire quality from the patients' perspective (QPP), and assess the construct validity of this version. Quality from the patients' perspective assesses 4 dimensions of quality of care. Involving discussion with user representatives, the QPP short version was adapted by adding 7 context-specific questions based on items from the Expanded Prostate Cancer Index Composite for Clinical Practice. This short version was answered on smartphone or tablet by 265 patients. We used exploratory factor analysis to assess dimensionality. For comparison with previous publications of the QPP, the analysis was repeated after mean imputation of missing values. The factor analysis identified 7 factors among the 30 analyzed items included in the analysis, explaining 64.9% of the variance. After imputation of missing, 2 factors explained 48.6% of the variance. None of these analysis captured the 4 dimensions of the QPP.